REKONSEPSI LITERASI AL-QUR’AN DALAM PENANAMAN NILAI MODERASI BERAGAMA PADA LINGKUNGAN KELUARGA - Sudirman Sudirman (Pascasarjana IAIN Sorong, 2022)
The focus of this research is on the reconception of Al-Qur'an Literacy to increase the understanding of religious moderation in the family environment. This study uses a literature review that compiles the concept of moderation in religion through the family. Several quotations of verses and hadiths are the basis for constructing this research, especially in instilling the values of religious moderation in the family environment. This study also confirms that religious moderation must be instilled in the family from an early age. This research also reveals that many verses make the role of the family in providing the inculcation of good values, especially in the family, especially in religious moderation. Early moderation in the family has more impact on understanding differences in society